A Role of Literacy in Raising Awareness of Waqf for Sustainable Development - Erwin Dariyanto (Sustainability Science and Resources)
Indonesia has a very large waqf potential, namely 57,763 hectares of land spread across 440,512 locations. Likewise, the potential for cash waqf reaches IDR 180 trillion per year. Another fact is that the majority of Indonesia's population, namely 87.08 percent or around 245,973,915 people, are Muslim.